EFFECTIVENESS OF TEACHING TOURISM TERMS INTENSIVELY (American Journal of Pedagogical and Educational Research, 2023)
This article is about intensive teaching strategies that are useful and essential one in education to conduct the lessons which teaches terms especially tourism terms in appropriate way. Much has been done and is being done in our country and abroad to intensify foreign language teaching. This has led to the development of new intensive methods and techniques. Intensive teaching of tourism terms is the process of teaching students to use tourism terms in appropriate way, in a short period of time.